From Empire to Identity: Linguistic Hybridity in Postcolonial English Literature" - Rasool Mohammed Abdulhussein Al-Muslimawi (مجلة الباحث, 2025)
Language is very important in terms of identity, especially in post-colonial setting since it functions as a colonial instrument and a cultural weapon. This study examines the linguistic hybridity in post-colonial literature and answers how authors incorporate native linguistic features into English to construct the cultural identity and challenge the colonial histories. This examination is based on the linguistic theories of Homi Bhabha, Edward Said, and Nguge wa Thiong’o. The research analyzes key works such as Things Fall Apart by Chinua Achebe, Midnight’s Children by Salman Rushdie, The God of Small Things by Arundhati Roy, and A Grain of Wheat by Nguge wa Thiong’o. It highlights the challenge between linguistics and challenges linguistic imperialism by transforming English into a means of postcolonial expression, considering the implications of hybridity in English Language Teaching (ELT) in the post-colonial countries. Final findings show that post-colonial writers reshape English to shift its role from a tool of colonial domination it a means of cultural resistance that reflects their hybrid identities